Serum Cathepsin S Is Associated With Decreased Insulin Sensitivity and the Development of Type 2 Diabetes in a Community-Based Cohort of Elderly Men - Jobs, Elisabeth (American Diabetes Association, 2013)
OBJECTIVE: To investigate associations between serum cathepsin S, impaired insulin sensitivity, defective insulin secretion, and diabetes risk in a community-based sample of elderly men without diabetes. RESEARCH DESIGN AND METHODS: Serum cathepsin S, insulin sensitivity (euglycemic-hyperinsulinemic clamp), and insulin secretion (early insulin response during an oral glucose tolerance test) were measured in 905 participants of the Uppsala Longitudinal Study of Adult Men (mean age, 71 years). Thirty participants developed diabetes during 6 years of follow-up. RESULTS: After adjustment for age, anthropometric variables, and inflammatory markers, higher cathepsin S was associated with decreased insulin sensitivity (regression coefficient per SD increase −0.09 [95% CI −0.14 to −0.04], P = 0.001), but no association with early insulin response was found. Moreover, higher cathepsin S was associated with a higher risk for developing diabetes (odds ratio per SD increase 1.48 [1.08–2.01], P = 0.01). CONCLUSIONS: Cathepsin S activity appears to be involved in the early dysregulation of glucose and insulin metabolism.